Hotspots and future trends of dermatofibrosarcoma protuberans - Meng, Zhen; Zhang, Rui; Sun, Zhihong; Fu, Cong; Li, Zhiyu; Wang, Luying; Huo, Ran; Xue, Feng (Frontiers in Oncology, 2024)
ObjectiveDermatofibrosarcoma protuberans (DFSP) is a moderately malignant soft tissue sarcoma with localized infiltrative growth. The extensive surgical scope and high recurrence rate of DFSP brings dysfunctional, aesthetic, psychological and economic problems to patients. The aim of this study is to explore the global publication characteristics, research hotspots and future trends of DFSP over the past 32 years via an intuitive visualized way.MethodsThe Web of Science Core Collection (WoSCC) database was searched for papers related to DFSP published from 1990 to 2022. Then bibliometric analysis of these publications was performed, including collaborative networks, co-citation analysis of journals and references, and cluster analysis of keywords.ResultsA total of 1588 papers were retrieved between 1990-2022. The United States was the most prolific country, followed by China. The article Imatinib Mesylate in Advanced Dermatofibrosarcoma Protuberans: Pooled Analysis of Two Phase II Clinical Trials, received most citations. Research hotspots and future trends are mainly focused on disease diagnosis, COL1A1-PDGFB fusion gene, drug and surgical treatment, fibrosarcomatous transformation, and immunotherapy.ConclusionThe research on DFSP faces several clinical challenges. This study provides novel insights into future research directions and scientific decisions for DFSP.